PENERAPAN TRANSPARANSI MELALUI WEBSITE (www.jakarta.go.id) PEMERINTAH PROVINSI DKI JAKARTA (PERIODE TAHUN 2017-2018) - Annisa Eka Puspitasari; Priyatno Harsasto (Journal of Politic and Government Studies, 2019)
Open government is one manifestation of good governance. This is also done by the DKI Jakarta Provincial Government to implement open government by using official local government websites. So this study aims to find out how the application of transparency is manifested in the appearance of the website, then the features used in the dissemination of the transparency of the policy and policy agenda that affect the management of the website. The research method used is descriptive qualitative using data collection techniques such as observation, interviews, literature studies, and document review. The results of this study are that the application of transparency is carried out by the availability of various kinds of public aspirations services and the existence of websites related to all SKPD. Use of features regarding policy transparency, with the application of e-budgeting and e-musrenbang. The existence of a continuation of previous government policies and changes in policies related to transparency of policies such as management of Jakarta Smartcity services and the use of a CRM system (Citizen Relation Management). The conclusion of this study regarding the transparency of policy on the official website of the DKI Jakarta Provincial Government has been good with 17 information indicators that only two are not yet available. The feature of the spread of transparency is said to be good in the presence of various kinds of availability and ease of access to information such as the presence of eight (8) complaint channels. implementing rules and recruitment of executing officials that show good things due to changes in the settlement of complaints by directly pointing to the lurah as the executor of the program (admin) which shows the command and control directly. The existence of transparency service innovations such as the open data portal, PTSP services through the Public Service Mall. However, there are still inhibiting factors in the implementation of transparency such as public support which can be seen from the number of participating in the website usage and the low management resources. Keywords: open government, public service, public policy